Detection of moderate to high antiphospholipid antibodies by chemiluminescence meets 2023 APS classification criteria - Jiang, Haiyue; Yang, Yaqing; Tang, Zihan; Pan, Haoyu; Liu, Honglei; Cheng, Xiaobing; Su, Yutong; Ye, Junna; Hu, Qiongyi; Meng, Jianfen; Chi, Huihui; Zhou, Zhuochao; et al. (Scientific reports, 2025)
The 2023 ACR/EULAR criteria for antiphospholipid syndrome (APS) have modified the laboratory domain. However, enzyme-linked immunosorbent assay (ELISA) remains the sole specified method for antiphospholipid antibody detection. This study aims to establish moderate and high levels of anticardiolipin(aCL) and anti-β2-glycoprotein I antibodies (anti-β2GPI) using chemiluminescence assay (CIA) and to investigate the diagnostic efficiency and risk stratification capabilities of CIA in comparison to ELISA. We conducted a comprehensive analysis involving 166 APS patients, 194 disease controls, and 120 healthy controls. Our assessment entailed the utilization of both ELISA and CIA to detect aCL IgG/IgM and anti-β2GPI IgG/IgM. We established distinct moderate and high semi-quantitative thresholds for CIA corresponding to ELISA. Additionally, we computed the likelihood ratios at various thresholds and compared them with ELISA. The qualitative agreement and quantitative correlation between CIA and ELISA were robust. When applying the established moderate and high thresholds of aCL/aβ2GPI IgG/IgM in CIA according to the equal ROC specificity corresponding to ELISA, the diagnostic efficiency and risk stratification capabilities of CIA aligned comparably with those of ELISA. Although IgM exhibited poorer performance in risk assessment compared to IgG, it still played as risk factors for thrombosis and obstetrical manifestations. Utilizing the established moderate/high thresholds for aCL/aβ2GPI IgG/IgM by CIA, effectively addressing both diagnostic and risk stratification requirements comparable to ELISA, signifies that the CIA has emerged as an alternative for aPL detection. The high specificity and clinical relevance of aCL/aβ2GPI IgM in clinical events highlight its importance in clinical practice.